A DISTOPIA DA UBERIZAÇÃO: Flexibilização e precarização do trabalho nos serviços de delivery e transporte por aplicativos no Brasil a partir de 2014 - GARCEZ, Railson Marques (2021)
The crisis scenario of capital and the major socioeconomic, cultural and political transformations that the globalized and digitalized economy is undergoing have brought to the arena of debate new discussions and new dilemmas regarding the metamorphosis of work in this century. Uberization, as a concrete manifestation of platform capitalism, is at the epicenter of current discussions and presents itself as a phenomenon that brings together ideals of freedom, autonomy, self-management, and flexibility for the "partners" logged into the digital platforms. We start from the hypothesis that the phenomenon of uberization in contemporary capitalism spreads through the appfication of delivery and transportation services while expanding the process of labor precarization on the platforms. It is by considering the advance of platform capitalism and appfication, illustrated mainly by digital labor platforms that are used to extract surplus value and print a new type of modern slavery, that this paper sought to understand the central elements of uberization and how this phenomenon contributes to a greater precarization of delivery and transportation platform workers in Brazil since 2014. To achieve this goal, a qualitative and quantitative approach was used, including bibliographic research, in order to ground the discussion categories, and data analysis of PNAD and PNAD COVID 19. Considering the problem raised and the data presented, we conclude that the uberization of work is a new form of domination of contemporary capitalism that manifests itself through work practices perceived as more flexible, but more precarious in digital platforms, known as apps. The unfoldings of the covid-19 pandemic in Brazil so far also suggest an intensification of the precarization dynamics of workers on delivery and transportation platforms, considered essential services in the midst of social isolation measures. Therefore, one can understand the phenomenon of uberization as a model that updates the format of labor exploitation, transfers costs and risks to the worker, updates labor precarization and, above all, as a global but dystopian reality in contemporary capitalism.